Aluminum Produce System of PD. Jaya Metal Aluminum With Visual Basic 6.0 - Ridwan Octavianus (Jurnal Sistem Informasi, 2004)
In relation to aluminum ordering system is still one part of the supply system, therefore the implementation of computerization is very important to speed up the process of data acquisition. Therefore, this ordering system will be used for the achievement of aluminum demand could be met in this writing may be presented to the public sepraktis can use this booking system as a reference, which can then be developed according to needs, and may be used by for all especially for the beginner those who already understand the basics of information systems